Exploring the Use of Digital Marketing as a Basis for Financial Decisions for MSMEs in Serdang Bedagai Regency - Edy Firmansyah; Erbin Sitorus; Anto Tulim (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
Digital transformation has shifted the role of digital marketing from merely a promotional tool to a strategic source of information that supports business decision-making in Micro, Small, and Medium Enterprises (MSMEs). However, the effective utilization of digital data remains constrained by several factors, including customer data relevance, digital literacy, and technology implementation. This study aims to examine the effects of customer data relevance, digital literacy, and technology implementation on the quality of MSME financial decisions in Serdang Bedagai Regency. A quantitative approach employing multiple linear regression analysis was used. Data were collected through questionnaires administered to 100 MSMEs that actively utilize digital media in their business operations. The analysis included validity and reliability tests, classical assumption tests, t-tests, F-tests, and the coefficient of determination. The findings reveal that digital literacy is the only variable that has a positive and statistically significant effect on the quality of MSME financial decisions, the calculated t-value of the digital literacy variable is 8.993, this value is greater than the t-table value of 1.661, the Sig value of 0.003 is greater than 0.05, meanwhile customer data relevance and technology implementation do not have significant partial effects. Nevertheless, the three independent variables jointly have a significant influence on the quality of MSME financial decisions. These findings suggest that the success of digital transformation in supporting financial decision-making depends primarily on the digital competencies of MSME owners rather than solely on the availability of relevant customer data or technological support. This study contributes to the literature on digital transformation by highlighting the critical role of digital literacy in enabling data-driven financial decision-making among MSMEs.